The Processes of Violent Disintegration and Natural Creation of Matter in the Universe - Weitter Duckss (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
This article completes the circle of presenting the process of the constant growth of objects and systems and the topics to complete it consist of the visible matter violent disintegration and its re-creation inside the Universe. A constant process of the visible matter disintegration is presented as the end of the process, the proportions of which are gigantic, and the creation of the visible matter as the beginning of it. The disintegration of particles disturbs the balance of the Universe's wholeness; despite the enormous loss of the visible matter, the Universe is constantly growing. After having postponed it for a while, this article discusses the age of objects and the Universe as a consequence of the process of the constant matter growth. The acquired results are completely different from those, offered by the renowned experts of the time.